Value of Contrast-Enhanced Ultrasound and Acoustic Radiation Force Impulse Imaging for the Differential Diagnosis of Benign and Malignant Thyroid Nodules - Yan He; Xiao Yan Wang; Qiao Hu; Xue Xue Chen; Bing Ling; Hai Ming Wei (Frontiers Media S.A., 2018)
Objectives: To assess the value of contrast-enhanced ultrasound (CEUS) and acoustic radiation force impulse (ARFI) imaging for the differential diagnosis of benign and malignant thyroid nodules.Methods: CEUS was performed in eighty-eight thyroid nodules. The patterns of CEUS were analyzed, and ARFI was then performed. The shear wave velocities (SWVs) of the nodules and the surrounding normal thyroid tissue were obtained. The areas under the curve (AUCs) and cut-off value were obtained by a receiver operating characteristic (ROC) curve analysis. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic rate of each modality were assessed and compared using pathological diagnosis.Results: Among 88 nodules, 29 nodules were malignant and 59 were benign. The sensitivity, specificity, PPV, NPV, and diagnostic rate of CEUS were 79.3, 91.5, 82.1, 90, and 87.5%, respectively. Using a cut-off value of 2.565 m/s for SWV, the sensitivity, specificity, PPV, NPV and diagnostic rate for malignancy were 75.9, 94.9, 88.0, 88.9, and 88.6%, respectively. The AUC was 0.878. The sensitivity, specificity, PPV, NPV and diagnostic rate of CEUS in combination with ARFI were 93.1, 89.8, 81.8, 96.3, and 90.9%, respectively.Conclusion: Both CEUS and ARFI are valuable for the differential diagnosis of benign and malignant thyroid nodules. Combining these two methods can improve the diagnostic rate.